Paradoks Kewirausahaan Di Indonesia, Sebuah Peluang Atau Keterpaksaan? Studi Empiris Menggunakan Data Sakernas Tahun 2017 - Beni Teguh Gunawan (Jurnal Ketenagakerjaan, 2018)
The unbalanced number of job seeker and employment cause employment opportunity. Large numbers of unemployment can cause problems in some country. An alternative to decrease the unemployment is to encourage entrepreneurship. However, for some people, entrepreneurship is considered to be the last resort for job seeker who are not absorbed into formal employment. The objective of this paper is to determine the paradox of entrepreneurship. In one side, entrepreneur is a last resort for the which is not absorbed in some formal job, in another side, entrepreneur is a promising choice. From the results of quantitative analysis we got the fact that entrepreneurship is a promising and reliabe for almost labour force. Although actually people who work as workers more than entrepreneurs. Quantitative analysis results show that only 25.5% of entrepreneurs feel entrepreneurial as a last resort, while 74.5% of entrepreneurship is an opportunity.